Health literacy and health behaviors 3E 2S of public sector executives, Phra Nakhon Si Ayutthaya province - ไพบูลย์ศิริ, พิทยา (Journal of Preventive Medicine Association of Thailand, 2018)
The objective of this cross-sectional descriptive study is to know health literacy and health behaviors 3E 2S and the relationship of health literacy and health behaviors of public sector executives. The samples were 84 public sector executives working in Phra Nakhon Si Ayutthaya province. Data were collected from January to March 2018. The research tool was health literacy and health behaviors 3E 2S among working group aged 15-59 evaluation form of Health Education Section, Health Service Support Department, Ministry of Public Health. The data were analyzed using descriptive statistics in percentages, means and standard deviations and using Exact test and Spearman’s correlation to test the relationships. The findings revealed that 73.81% had moderate health literacy, 52.38% had moderate health behaviors. Using tests for relationships, personal factors were not statistical significantly related to health literacy, but showed statistical significant in relationship observed between health literacy and health behaviors (r=0.4824; p=<0.001). The results of this study are beneficial to further strengthening health literacy and health behaviors of public sector executives.